A Companion to Michael Oakeshott - Abel, Corey; Boucher, David; Corey, Elizabeth; Devigne, Robert; Franco, Paul; Franco, Paul; Fuller, Timothy; Gerencser, Steven; Grant, Robert; Malcolm, Noel; Marsh, Leslie; Marsh, Leslie; et al. (Penn State University Press, 2021)
Michael Oakeshott has long been recognized as one of the most important political philosophers of the twentieth century, but until now no single volume has been able to examine all the facets of his wide-ranging philosophy with sufficient depth, expertise, and authority. The essays collected here cover all aspects of Oakeshott's thought, from his theory of knowledge and philosophies of history, religion, art, and education to his reflections on morality, politics, and law. Aside from the editors, the contributors are Corey Abel, David Boucher, Elizabeth Corey, Robert Devigne, Timothy Fuller, Steven Gerencser, Robert Grant, Noel Malcolm, Kenneth McIntyre, Kenneth Minogue, Noël O'Sullivan, Geoffrey Thomas, and Martyn Thompson